Design and Simulation Low Noise Amplifier at 5.8GHz for WIMAX Applications - Ibrahim, Abu Bakar; Othman, Abdul Rani; Husain, Mohd Nor; Johal, Mohamad Syahrir (2011)
This paper presents a 5.8 GHz Low Noise Amplifier (LNA) design with cascode and cascaded techniques using T-matching network applicable for IEEE 802.16 standard. The amplifier use FHX76LP Low Noise SuperHEMT FET. The design simulation process is using Advance Design System (ADS) software. The cascode and cascaded low noise amplifier (LNA) produced gain of 53.1dB and noise figure (NF) of 1.17dB. The input reflection (S11) and output return loss (S22) are -19.77dB and -10.07dB respectively .The input sensitivity is compliant with the IEEE 802.16 standards.